A review on indoor green plants employed to improve indoor environment. (1st August 2022) - Liu, Fudan; Yan, Lianyu; Meng, Xi; Zhang, Cen
Abstract: With the urban development, indoor air quality (IAQ) is of growing public health concern due to that fact people spend 80%–90% of their time indoors, which has prompted the use of plants to reduce the air pollution through the phytoremediation from interior spaces, especially in the enclosed rooms with air-conditioning and heating. Indoor plants have been proved to improve the indoor environment, relieve anxiety, and reduce CO2 concentration. However, the comprehensive review has not been published to summarize the development status and potential deficiencies of indoor green plants after 2018. The 50 published articles related to indoor green plants were selected by the primary retrieval system and the later manual screening. This review mainly focused on the effects of green plants on the indoor thermal environment and indoor pollutants including volatile organic compounds (VOCs), and CO2 concentration, while the application efficiency of green plants was described on learning or productivity efficiency, patients' post-operative recovery and emotion comprehensively. Highlights: A detailed illustration was provided on indoor green plants. Effects of indoor plants on indoor environment were comprehensive evaluated. Indoor plants showed a great potential in the psychological aspect. Future directions were discussed on the possible studies and applications.